Biofilm Formation of Staphylococcus aureus from Pets, Live-Stock, and Wild Animals - Silva, Vanessa (2022)
Funding: NORTE-01-0145-FEDER-030101 the projects UIDB/CVT/00772/2020 and LA/P/0059/2020 funded by the Portuguese Foundation for Science and Technology (FCT). The Ministerio de Ciencia, Innovación y Universidades (Spain, grant number RTI2018-098267-R-C33) and the Junta de Castilla y León (Consejería de Educación, Spain, grant number LE018P20). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.